Dose Effect and Mode of Inheritance of Diabetogenic Gene on Mouse Chromosome 11. (25th February 2013) - Babaya, Naru; Ueda, Hironori; Noso, Shinsuke; Hiromine, Yoshihisa; Nojima, Koji; Itoi-Babaya, Michiko; Kobayashi, Misato; Fujisawa, Tomomi; Ikegami, Hiroshi
Abstract : The quantitative trait locus (QTL) mapping in segregating crosses of NSY (Nagoya-Shibata-Yasuda) mice, an animal model of type 2 diabetes, with nondiabetic strain C3H/He mice has identified diabetogenic QTLs on multiple chromosomes. The QTL on chromosome 11 (Chr11) ( Nidd1n ) showing the largest effect on hyperglycemia was confirmed by our previous studies with homozygous consomic mice, C3H-11 NSY, in which the NSY-derived whole Chr11 was introgressed onto control C3H background genes. C3H-11 NSY mice also showed a streptozotocin (STZ) sensitivity. In the present study, we constructed heterozygous C3H-11 NSY mice and the phenotypes were analyzed in detail in comparison with those of homozygous C3H-11 NSY and C3H mice. Heterozygous C3H-11 NSY mice had significantly higher blood glucose levels and STZ sensitivity than those in C3H mice. Hyperglycemia and STZ sensitivity in heterozygous C3H-11 NSY mice, however, were not as severe as in homozygous C3H-11 NSY mice. The body weight and fat pad weight in heterozygous C3H-11 NSY mice were similar to those in C3H and homozygous C3H-11 NSY mice. These data indicated that the introgression of Chr11 of the diabetes-susceptible NSY strain onto diabetes-resistant C3H caused marked changes in the glucose tolerance and STZ susceptibility even in a heterozygous state, and suggested that the mode of inheritance of a gene or genes on Chr11 for hyperglycemia and STZ sensitivity is additive.